From mitochondria to sarcopenia: role of 17β-estradiol and testosterone - Tian, Xu; Lou, Shujie; Shi, Rengfei (Frontiers in Endocrinology, 2023)
Sarcopenia, characterized by a loss of muscle mass and strength with aging, is prevalent in older adults. Although the exact mechanisms underlying sarcopenia are not fully understood, evidence suggests that the loss of mitochondrial integrity in skeletal myocytes has emerged as a pivotal contributor to the complex etiology of sarcopenia. Mitochondria are the primary source of ATP production and are also involved in generating reactive oxygen species (ROS), regulating ion signals, and initiating apoptosis signals in muscle cells. The accumulation of damaged mitochondria due to age-related impairments in any of the mitochondrial quality control (MQC) processes, such as proteostasis, biogenesis, dynamics, and mitophagy, can contribute to the decline in muscle mass and strength associated with aging. Interestingly, a decrease in sex hormones (e.g., 17β-estradiol and testosterone), which occurs with aging, has also been linked to sarcopenia. Indeed, 17β-estradiol and testosterone targeted mitochondria and exhibited activities in regulating mitochondrial functions. Here, we overview the current literature on the key mechanisms by which mitochondrial dysfunction contribute to the development and progression of sarcopenia and the potential modulatory effects of 17β-estradiol and testosterone on mitochondrial function in this context. The advance in its understanding will facilitate the development of potential therapeutic agents to mitigate and manage sarcopenia.